2013
DOI: 10.1210/jc.2012-4050
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Rituximab in a Case of Riedel's Thyroiditis Refractory to Glucocorticoids and Tamoxifen

Abstract: A 42-year-old woman presented with a rapidly enlarging right-sided thyroid mass and underwent hemithyroidectomy. Riedel's thyroiditis was only diagnosed upon surgical decompression of the right carotid artery 2 years later. She became more symptomatic as Riedel's thyroiditis progressed, and mediastinal fibrosclerosis developed over the next 12 months. Oral prednisolone failed to improve her condition, and she was commenced on tamoxifen. Despite initial improvement, her symptoms recurred 2 years later, mainly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…On the other hand, findings from a recently conducted single‐arm trial of rituximab used for IgG4‐RD have shown promising results in terms of remission of disease . While no patient with RT has been included in that trial, we are aware of one case report that describes the effective use of rituximab in a single RT patient refractory to tamoxifen and glucocorticoid treatment . Unfortunately, no other trial of antifibrotic therapy for RT has been completed to date.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, findings from a recently conducted single‐arm trial of rituximab used for IgG4‐RD have shown promising results in terms of remission of disease . While no patient with RT has been included in that trial, we are aware of one case report that describes the effective use of rituximab in a single RT patient refractory to tamoxifen and glucocorticoid treatment . Unfortunately, no other trial of antifibrotic therapy for RT has been completed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid investigations in patients with hematological disorders have essentially focused on the thyroid complications ensuing from chemotherapy and/or external irradiation (4)(5)(6)(7)(8)(9)(10)14,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Because no study has simultaneously taken care of all clinically relevant thyroid aspects (namely, function, autoimmunity and nodules), we have conducted such a study on hematoncologic patients excluding those who had been treated with external irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, extra-thyroid organ involvement and the presence of IgG4-positive plasma cells both predict a good response to steroid therapy in patients with RT. In patients refractory to the steroid therapy, tamoxifen and rituximab have been reported to be effective [7,30,31].…”
Section: Discussionmentioning
confidence: 99%